Time‐Dependent T1–T2 Switchable Magnetic Resonance Imaging Realized by c(RGDyK) Modified Ultrasmall Fe3O4 Nanoprobes. (22nd June 2018) - Bai, Chen; Jia, Zhengyang; Song, Lina; Zhang, Wei; Chen, Yi; Zang, Fengchao; Ma, Ming; Gu, Ning; Zhang, Yu
Abstract: To achieve the accurate diagnosis of tumor with the magnetic resonance imaging (MRI), nanomaterials‐based contrast agents are developed rapidly. Here, a tumor targeting nanoprobe of c(RGDyK) modified ultrasmall sized iron oxide is reported with high saturation magnetization and high T1 ‐weighted imaging capability, attributed to a large number of paramagnetic centers on the surface of nanoprobes and rapid water proton exchange rate (inner sphere model), as well as strong superparamagnetism (outer sphere model). These nanoprobes could actively target and gradually accumulate at the tumor site with a time‐dependent T1 –T2 contrast enhancement imaging effect. In in vivo MRI experiments, the nanoprobes exhibit the best T1 contrast enhancement at 30 min after intravenous administration, followed by gradually vanishing and generating T2 contrast enhancement with increasing time at tumor site. This is likely due to time‐dependent nanoprobes aggregation in tumor, in good agreement with in vitro experiment where aggregated nanoprobes display larger r 2 / r 1 value (19.1) than that of the dispersed nanoprobes (2.8). This dynamic property is completely different from other T1 ‐T2 dual‐modal nanoprobes which commonly exhibit the T1 ‐ and T2 ‐weighted enhancement effect at the same time. To sum up, these c(RGDyK) modified ultrasmall Fe3 O4 nanoprobes have significant potential to improve the diagnostic accuracy and sensitivity in MRI. Abstract : Time‐dependent T1 –T2 contrast enhancement magnetic resonance imaging can be achieved by gradual accumulation of c(RGDyK) modified ultrasmall sized Fe3 O4 nanoprobes in tumor, leading to transforming from dispersive to aggregated state. In in vivo MRI experiments, after intravenous administration with these nanoprobes, the best T1 contrast enhancement exhibited at 30 min, followed by gradually vanishing and generating T2 contrast enhancement with increasing time at tumor site.